Investigation of Carriers of Salmonella and Other Hydrogen Sulphide-Positive Bacteria in the Digestive Content of Fish from the Atlantic Area of Macaronesia: A Comparative Study of Identification by API Gallery and MALDI-TOF MS - Inmaculada Rosario Medina; Marco Antonio Suárez Benítez; María del Mar Ojeda-Vargas; Kiara Gallo; Daniel Padilla Castillo; Miguel Batista-Arteaga; Soraya Déniz Suárez; Esther Licia Díaz Rodríguez; Begoña Acosta-Hernández (Animals)
Salmonella spp. are known pathogens in fish, with their presence potentially resulting from the contamination of the aquatic environment or improper handling. Accurate bacterial identification is crucial across various fields, including medicine, microbiology, and the food industry, and thus a range of techniques are available for this purpose. In this study, Salmonella spp. and other hydrogen sulphide-positive bacteria were investigated in the digestive contents of fish destined for consumption from the Atlantic area of Macaronesia. Two identification techniques were compared: the traditional API method and the MALDI-TOF MS technique. For the identification of Salmonella spp. carriers, 59 samples were processed following ISO 6579–1:2017. A total of 47 strains of Gram-negative bacilli were obtained. No Salmonella spp. isolates were detected. The most frequent genus was Enterobacter (76.50%), followed by Shewanella (10.63%). The MALDI-TOF MS technique showed a high concordance with the API technique, with 72.34% concordance at the species level. Both techniques demonstrated a high degree of concordance in the identification of Enterobacter cloacae, with 87.23% genus-level concordance and 12.76% non-concordant identifications. This study highlights the limitations of the API technique and the speed and precision of MALDI-TOF MS. The identified bacteria could pose a health risk to humans.